Is it possible to use the Toll-like receptors as biomarkers for neonatal sepsis? Review of the recent literature - Irina Melinda Baizat; Corina Gabriela Zaharie; Monica Hasmasanu; Melinda Matyas; Lucia Maria Procopciuc (Amaltea Medical Publishing House, 2022)
Background. Sepsis continues to be one of the main death causes in the neonate population. The toll-like receptors are molecules that express in the plasma or endosomal membrane and recognize endosomal or microorganism components. While aiming at the identification of new neonatal sepsis biomarkers, the toll-like receptors (TLR) have been considered that some of them overexpress in contact with the bacterial components. Methods. Research in the PubMed database has been made by the following criteria: Inclusion criteria (PubMed database, Period 2005-2022, English & Humans, generated 29, Meta-Analysis - 0, Review - 6, Systematic Review - 0), Exclusion criteria (Studies on animal models, Articles with merely didactical content, Articles regarding only one of the words researched either only neonatal sepsis or TLR in another context than together, Articles that are not directly connected with the topic). Based on the above-mentioned criteria 13 articles were consulted, of which 7 articles included in vivo studies, 6 with in vitro studies. Conclusions. The data of the present review and the current diagnostic method point at the fact that TLRs increase in the conditions of the presence of the inflammatory syndrome. Their dosing during in the neonatal sepsis is possible, but the non-specific overexpression is not a diagnostic.